Electrodiagnostic findings in myotonic dystrophy: A study on 12 patients - Ahmet S. Burakgazi (MDPI AG, 2019)
Myotonic dystrophy (DM) is a complex multisystem disease with specific clinical and electrodiagnostic findings. Myotonia can be seen in the distal and proximal muscle groups in upper and lower limbs. There is no established guideline to demonstrate the sensitivity of muscles in the diagnosis of myotonic dystrophy. The aims of this study are to describe common electrodiagnostic findings in patients with DM; and to assess the electrodiagnostic sensitivity of muscles in the diagnosis of DM. In this retrospective study, patients' age, sex, nerve conduction study findings including common upper and lower limbs nerve functions, and needle examination findings were collected and analyzed. A descriptive analysis (with percentage) was performed on the data obtained from the charts. NCS analysis showed more than half of patients had normal sensory and motor NCS findings. In 11 over 12 patients, sensory NCSs were within normal limits. Only one patient showed abnormal sensory responses. The most common abnormal NCS findings were decreased amplitude with normal latency and normal conduction velocity. The needle analysis showed distal muscles including first dorsal interosseous, abductor policies brevis, tibialis anterior, medial gastrocnemius and peroneal longus muscles are more sensitive in detecting myotonic discharges than proximal muscles including deltoid, triceps, vastus medialis and vastus lateralis. Our findings showed sensory nerve responses were usually within normal limits. The most common NCS abnormality showed decreased motor nerve amplitudes. The needle test showed myotonic discharges were more prominent in the distal muscles in upper and lower limbs.